Representation of the Sámi Culture in Tourism in Sweden: : A Thematic Analysis of Marketing Websites from Swedish Lapland - Ticao Hernaez, Gynn Heissy; Mavromatis Klempin, Lukas (Högskolan Dalarna, Turismvetenskap, 2018)
The following thesis examines the representation of Sámi that reside in the Swedish part of Lapland. Tourism has been a complement to the traditional occupations for many Sámi. However, representations of Sámi in web-marketing may be misleading the tourists in their understanding of the Indigenous people. The aim of the thesis is to examine regional marketing material in Sweden, found online, through a thematic analysis to highlight patterns and themes that are utilized for a competitiveness in the market. The use of language, when referring to Sámi, and adjectives to describe landscape, food, and people were focused upon. Six webpages were analysed, which showed a strong focus of the marketing material on reindeer, languages, handicrafts and food.